Perspektif Masyarakat Mengenai Aplikasi untuk Pencegahan dan Penanganan COVID -19 di Jakarta - Rizky Farmasita B.; Tita Sidatunisa; Dedi Nugroho; Benny Efendie (Publikasi Indonesia, 2022)
The role of the community in preventing the COVID-19 virus is very necessary, therefore the role of information technology can help the community in handling and preventing the COVID-19 virus with information that can be accessed through mobile phone devices that can practically do contact tracing. . The purpose of this study is to find out what people think about applications for the prevention and treatment of COVID-19 that have been used in Indonesia and about the expected features of a user-friendly COVID-19 prevention and treatment application. This research method uses qualitative methods to conduct interviews with a sample of 25 subjects who live in Jakarta. The results of this study, several people have used the COVID-19 prevention and treatment application with the name of the application used is Peduli Protect, many think that this application is effective enough to be used to obtain a lot of information about COVID-19 and the public can do contact tracing. The conclusion of the study is that there are advantages and disadvantages to the Care Protect application and it is still necessary to add features in the Care Protect application.